2008
DOI: 10.1091/mbc.e07-11-1200
|View full text |Cite
|
Sign up to set email alerts
|

GRASP55 Regulates Golgi Ribbon Formation

Abstract: Recent work indicates that mitogen-activated protein kinase kinase (MEK)1 signaling at the G2/M cell cycle transition unlinks the contiguous mammalian Golgi apparatus and that this regulates cell cycle progression. Here, we sought to determine the role in this pathway of Golgi reassembly protein (GRASP)55, a Golgi-localized target of MEK/extracellular signal-regulated kinase (ERK) phosphorylation at mitosis. In support of the hypothesis that GRASP55 is inhibited in late G2 phase, causing unlinking of the Golgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
196
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(222 citation statements)
references
References 44 publications
12
196
2
3
Order By: Relevance
“…An appealing mechanism for intercisternal adhesion has been proposed for the GRASP proteins based on X-ray crystallography and biochemistry that involves PSD-95, Dlg1, Zo-1 domain-dependent homo-oligomerization in trans (13-15). In recent years, with the advent of RNAi-based technologies, knock-down studies have broadly confirmed a role for GRASP proteins and Golgins in controlling Golgi morphology but have not agreed with each other on many notable details, leaving the field in a somewhat confused and conflictory state (10,(15)(16)(17)(18)(19)(20). In the simpler case of Drosophila, dsRNA-mediated depletion of dGRASP results in ∼30% loss of Golgi stacks, whereas double depletion of dGRASP and dGM130 was shown to unstack the Golgi, as examined by EM (21).…”
mentioning
confidence: 99%
“…An appealing mechanism for intercisternal adhesion has been proposed for the GRASP proteins based on X-ray crystallography and biochemistry that involves PSD-95, Dlg1, Zo-1 domain-dependent homo-oligomerization in trans (13-15). In recent years, with the advent of RNAi-based technologies, knock-down studies have broadly confirmed a role for GRASP proteins and Golgins in controlling Golgi morphology but have not agreed with each other on many notable details, leaving the field in a somewhat confused and conflictory state (10,(15)(16)(17)(18)(19)(20). In the simpler case of Drosophila, dsRNA-mediated depletion of dGRASP results in ∼30% loss of Golgi stacks, whereas double depletion of dGRASP and dGM130 was shown to unstack the Golgi, as examined by EM (21).…”
mentioning
confidence: 99%
“…In addition to Golgi stacking, GRASP proteins have been implicated in lateral fusion of cisternae to form ribbon-like Golgi structures in mammalian cells (22,23) and in unconventional secretion pathways (24 -26). The membrane-tethering activity appears to be critical for the functions of GRASP proteins.…”
mentioning
confidence: 99%
“…This activity arose as the result of the tethering functions displayed by GRASP65 and GRASP55, through their interactions with their partner proteins GM130 and golgin-45, respectively (2)(3)(4). Several other studies have shown more recently that the GRASPs are involved in the maintenance of the structure of the Golgi ribbon in mammal cells during interphase, in controlling the fragmentation of the Golgi complex at the onset of mitosis (5)(6)(7)(8), in establishing cell polarity in migrating cells (9), and in the consumption of COPII vesicles and the formation of the cis-Golgi in yeast (10).…”
mentioning
confidence: 99%
“…Indeed, a direct role for GRASPs in cargo transport has so far been established only for the unconventional secretion routes in Dictyostilium and Drosophila (11,12), whereas they have been shown not to be directly involved in the trafficking of commonly studied reporter cargo proteins along the "conventional" secretory pathway (e.g. the temperature-sensitive (ts-045) mutant of the G protein of vesicular stomatitis virus (VSVG) 2 ) and secretory horseradish peroxidase (5,6,13,14). GRASPs can engage different types of interactions including the ones mediated by their PDZ domains, through which the GRASPs cannot only homodimerize, thus participating in cisternal stacking (15) but can also bind the C-terminal valine motifs (C-TVM) of membrane proteins such as protransforming growth factor ␣ and p24a (16,17).…”
mentioning
confidence: 99%